Synergistic Effects and Mechanisms of Combined Treatment With Harmine Hydrochloride and Azoles for Resistant Candida albicans - Li, Xiuyun; Wu, Xuexin; Gao, Yan; Hao, Lina (Frontiers in Microbiology, 2019)
Several studies have demonstrated its significant antiviral, antimicrobial, antiplasmodial, antioxidative, antifungal, antimutagenic, antitumor properties. Themain objective of the present study was to investigate the antifungal effects and underlyingmechanisms of harmine hydrochloride (HMH) when it was combined with azoles to determine whether these combinations act in a synergistic manner. In this study, we found that HMH exhibits synergistic antifungal effects in combination with azoles against resistant Candida albicans (C. albicans) planktonic cells as well as resistant C. albicans biofilm in the early stage, according to the microdilution method. Antifungal potential of HMH with fluconazole was also exploredin vivo using a novel invertebrate model. As for the synergistic mechanisms, it was revealed that this drug combination can decrease the efflux of azoles, inhibit the hypha growth and induce apoptosis of resistant C. albicans. Our results suggested that HMH combined with azoles are synergistic against resistant C. albicans in vitro and in vivo, and the synergistic mechanisms are involved in increasing the intracellular azoles, inhibiting the hyphal growth and inducing apoptosis of resistant C. albicans.